2000
DOI: 10.1007/s000110050576
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines trigger MUC gene expression and mucin release in the intestinal cancer cell line LS180

Abstract: Our data demonstrate differential cytokine effects on mucin synthesis, secretion and composition. These alterations may contribute to the defective mucus layer in colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 45 publications
11
95
2
Order By: Relevance
“…Treatment of cultured chondrocytes with tumor necrosis factor (TNF)-α or interleukin (IL)-1β was reported to increase TFF3 expression [34]. On the other hand, the expression of MUC6 (a core protein of GMC-type mucin) and the secretion of mucins were reported to be stimulated by TNF-α and IL-6 in the human colonic carcinoma-derived cell line LS180 [35]. The levels of TNF-α, IL-6, and IL-1β levels were reported to be elevated in the gastric mucosa in H. pylori-associated gastritis [36], and thus cytokine-mediated mechanisms may be involved in the upregulation of the expression of TFF2 and GMC-type mucin in the gastric mucosa in H. pylori-associated gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of cultured chondrocytes with tumor necrosis factor (TNF)-α or interleukin (IL)-1β was reported to increase TFF3 expression [34]. On the other hand, the expression of MUC6 (a core protein of GMC-type mucin) and the secretion of mucins were reported to be stimulated by TNF-α and IL-6 in the human colonic carcinoma-derived cell line LS180 [35]. The levels of TNF-α, IL-6, and IL-1β levels were reported to be elevated in the gastric mucosa in H. pylori-associated gastritis [36], and thus cytokine-mediated mechanisms may be involved in the upregulation of the expression of TFF2 and GMC-type mucin in the gastric mucosa in H. pylori-associated gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study conducted by Marillier and colleagues demonstrated goblet cell hyperplasia is observed independent of the IL‐13/IL‐4 signalling apparatus,62 and Muc2 and Muc3 transcripts were augmented even in the absence of IL‐4 during T. spiralis infection 50. Furthermore, inflammatory cytokines have been implicated to have a role in goblet cell function during parasitic infection, including IL‐1, TNF and IL‐22,63, 64, 65 and it is yet to be defined if microbial factors, the inflammasome and adrenergic and cholinergic receptors can influence the secretion of mucins and other goblet cell‐associated products during parasitic invasion.…”
Section: Immune Control Against Gi Nematode Infectionmentioning
confidence: 99%
“…This is linked to the depletion of goblet cells and downregulation of mucin production which could be influenced by immunological or bacterial factors during inflammation. In vitro study has revealed that pro-inflammatory cytokines IL-1, IL-6 or tumor necrosis factor (TNF)-α can cause an increased synthesis of MUC2 and other secretory mucins whereas incubation of individual cytokine additionally results in decreased and altered glycosylation in human goblet cell-like cells [27] . The elevated number of bacteria detected within the colonic mucus layer of UC patients poses another threat to the intestinal mucosa.…”
Section: Cathelicidin and Inflammationmentioning
confidence: 99%